Kepuasan Pasien Memediasi Pengaruh HEALTHQUAL terhadap Repurchase Intention pada Rumah Sakit Murni Teguh Sudirman Jakarta - Jayalie, Vito Filbert; Tecoalu, Melitina; Fushen, Fushen; Wahyoedi, Soegeng (Universitas HKBP Nommensen, 2023)
Background: Regardless of recovery in the number of visits from the pandemic to the new normal and post-pandemic era, hospitals need to ensure that patients who have come to the hospital are willing to visit for a second time (repurchase intention). Repurchase intention is influenced by patient satisfaction and quality of services. There are several tools to assess quality of hospital service, such as HEALTHQUAL questionnaire. There has been no research linking HEALTHQUAL, patient satisfaction, and repurchase intention. Objective: This research aims to study the association between HEALTHQUAL and repurchase intention, mediated by patient satisfaction. Methods: This research was a cross-sectional study at a private hospital in Jakarta (December 2022-January 2023). Statistical analysis was performed using SmartPLS software. Results: This study included 100 participants with a mean age of 40 years. Based on the questionnaire results, most of the patients agreed on questions about service quality and satisfaction. Model analysis showed that there was a significant association between HEALTHQUAL, patient satisfaction and repurchase intention (p<0.05; T-statistics>1.96). Moreover, patient satisfaction showed a significant mediator effect towards HEALTHQUAL and repurchase intention (p<0.001, T-statistics>1,96) Conclusion: HEALTHQUAL positively and significantly affects patient satisfaction and repurchase intention. Patient satisfaction also affects repurchase intention positively and significantly. Besides, patient satisfaction partially mediates the effect of HEALTHQUAL on repurchase intention. There is a positive effect of HEALTHQUAL mediated by patient satisfaction on repurchase intention.